Retinoic acid mediates long-paced oscillations in retinoid receptor activity: evidence for a potential role for RIP140. - Kelly C Heim; Joshua J Gamsby; Mary P Hever; Sarah J Freemantle; Jennifer J Loros; Jay C Dunlap; Michael J Spinella (PLoS ONE)
Background Mechanisms that underlie oscillatory transcriptional activity of nuclear receptors (NRs) are incompletely understood. Evidence exists for rapid, cyclic recruitment of coregulatory complexes upon activation of nuclear receptors. RIP140 is a NR coregulator that represses the transactivation of agonist-bound nuclear receptors. Previously, we showed that RIP140 is inducible by all-trans retinoic acid (RA) and mediates limiting, negative-feedback regulation of retinoid signaling. Methodology and findings Here we report that in the continued presence of RA, long-paced oscillations of retinoic acid receptor (RAR) activity occur with a period ranging from 24 to 35 hours. Endogenous expression of RIP140 and other RA-target genes also oscillate in the presence of RA. Cyclic retinoid receptor transactivation is ablated by constitutive overexpression of RIP140. Further, depletion of RIP140 disrupts cyclic expression of the RA target gene HOXA5. Evidence is provided that RIP140 may limit RAR signaling in a selective, non-redundant manner in contrast to the classic NR coregulators NCoR1 and SRC1 that are not RA-inducible, do not cycle, and may be partially redundant in limiting RAR activity. Finally, evidence is provided that RIP140 can repress and be induced by other nuclear receptors in a manner that suggests potential participation in other NR oscillations. Conclusions and significance We provide evidence for novel, long-paced oscillatory retinoid receptor activity and hypothesize that this may be paced in part, by RIP140. Oscillatory NR activity may be involved in mediating hormone actions of physiological and pathological importance.